Reviews. Issue 3 (1st September 2016) - Higgins-Desbiolles, Freya; Slocum, Susan L.; Gabay, Elizabeth; Vadi, Priya; Santos, Cristóvão Bomfim Silva Dos; Kaaristo, Maarja; Ivanov, Stanislav
THE FUTURE OF FOOD TOURISM: FOODIES EXPERIENCES, EXCLUSIVITY VISIONS AND POLITICAL CAPITAL, IAN YEOMAN, UNA MCMAHON-BEATTIE, KEVIN FIELDS, JULIA ALBRECHT AND KEVIN MEETHAN (EDS) (2015) Bristol, Channel View, xviii + 286 pp., ISBN: 9781845415372, p/bk, £34.95EDIBLE IDENTITIES: FOOD AS CULTURAL HERITAGE, RONDA L. BRULOTTE AND MICHAEL A. DI GIOVINE (EDS) (2014) Farnham, Ashgate, xiii + 237 pp., ISBN: 9781409442639, h/bk, £70.00CONTEMPORARY WINE STUDIES: DANCING WITH BACCHUS, GARETH MORGAN AND RICHARD TRESIDDER (2016) Abingdon: Routledge, xxiv + 223 pp., ISBN: 9781138784451, p/bk, £28.95AT THE CHEF'S TABLE: CULINARY CREATIVITY IN ELITE RESTAURANTS, VANINA LESCHZINER (2015) Stanford, CA, Stanford University Press, xiv + 256 pp., ISBN: 9780804787970, h/bk, £32.00TRUST, TOURISM DEVELOPMENT AND PLANNING, ROBIN NUNKOO AND STEPHEN L. J. SMITH (EDS) (2015) Abingdon: Routledge, xiv + 186 pp., ISBN: 9780415826013, h/bk, £85.00RESEARCHING HOSPITALITY AND TOURISM, BOB BROTHERTON (2015) 2nd ed., London: Sage, 336 pp., ISBN: 9781446287552, p/bk, £27.99PLANNING RESEARCH IN HOSPITALITY AND TOURISM, LEVENT ALTINAY, ALEXANDROS PARASKEVAS AND SOOCHEONG (SHAWN) JANG (2016) 2nd ed., London and New York: Routledge, 331 pp., ISBN: 9781138852167, p/bk, £32.99